Swords into plowshares : building peace through the United Nations - Lee, Roy S. K., 1938- (Nijhoff law specials ;, 2006)
This work brings together a number of contributions analyzing some of the most pressing issues in the present world, and suggests ways and methods to manage these problems. Topics covered are the decision-making in the UN Security Council; the position of the United States vis-a-vis the United Nations; human rights and economic and social development; sustainable development and human rights, democracy and others. The book hopes to influence the policy and decision makers to take the necessary action towards the solution of these problems.